PENERAPAN METODE QIROATI DALAM MENINGKATKAN KEMAMPUAN MEMBACA AL QUR’AN DI DUSUN SAMPANGAN, KALIANGKRIK - Kuni Afiyah; Fitriyatul Banat (Institut Agama Islam Syubbanul Wathon Magelang, 2024)
This community service program aims to address the quality gap in Qur'anic literacy among students (santri) in Sampangan Hamlet, Kaliangkrik, characterized by low reading fluency and poor comprehension of Tajwid science. The methodology employed was Participatory Action Research (PAR), which began with the Research phase (interviews) that confirmed the lack of standardized teaching methods in the three partner TPQs (Qur'anic Education Centers). The main Action was realized through the direct implementation of the Qiroati Method over a 30-day period. The Qiroati Method was selected for its emphasis on the fast and accurate reading process skill, aligning with tartil principles, covering stages from pre-volume to finishing, and utilizing a classical teaching system with rhythmic pacing (ketukan). Through active Participatory involvement, the program successfully enhanced the students' ability to read the Qur'an fluently and correctly according to Tajwid, while also re-educating local TPQ teachers on the correct methodology, ensuring the sustainability of improved Qur'anic education quality in the hamlet.